Overview of novel strategies for the delivery of anthracyclines to cancer cells by liposomal and polymeric nanoformulations - Alavi, Mehran; Varma, Rajender S (International journal of biological macromolecules, 2020)
Severe side effects and the rapid emergence of drug resistance in cancer cells are major problems in the chemotherapy utilizing anthracyclines, with a difference between cellular response at nano and micro scale levels. Understanding this situation is more complicated issue to attain efficient targeted formulations with low unexpected toxicity in patients. On nano-scale level, considering properties of nano-bio interaction in all relevant parts of the body may offer clue for suitable formulations. Four main strategies comprising PEGylation, surface charging, targeting, and stimuli responsiveness can be deployed to improve the liposomal and polymeric nanoformulations that can efficiently deliver common anthracyclines namely daunorubicin (DAU), doxorubicin (DOX), idarubicin (IDA), and epirubicin (EPI). Herein, the advances and challenges pertaining to the formulations of these anticancer drugs via liposomal and polymeric nanoformulations, are discussed.
Keywords: antracykliny; farmaceutická chemie; polymery; nádory; Liposomes; Nanoparticles; Neoplasms; Polymers; lidé; Chemistry, Pharmaceutical; Antineoplastic Agents; protinádorové látky; Anthracyclines; nanočástice; liposomy; Humans